Post-Harvest Handling and Germplasm Storage of Jatropha curcas L. and Pongamia pinnata (L.) Pierre using Seed Cryopreservation - Chaudhury, Rekha; Malik, S.K. (Indian Journal of Agroforestry, 2020)
Commercial utilization of tree borne oilseeds as biofuel resources is becoming increasingly important for developing economies especially India. To assess the existing genetic diversity and to ensure its availability for the improvement of these rather unconventional crops for emerging future needs their germplasm management is of high importance. In the present study post-harvest seed handling, seed storage, longevity and long-term storage were attempted in two species Jatropha curcas L. and Pongamia pinnata (L.) Pierre. Desiccation and freezing tolerance of seeds, embryos and embryonic axes was determined and critical moisture content level: was ascertained. Recovery growth of embryo/embryonic axes in vitro of the two species was standardized. The germplasm collected from different sources varied in seed characteristics Seeds, embryos and embryonic axes were tolerant to desiccation upto 5.8% moisture and to freezing upto -196Â°C. High survival obtained upto 540 days cryostorage promises a simple technology for long-term storage of diverse germplasm of Jatropha and pongamia. Seeds of jatropha showed longevity for relatively longer duration than pongamia, which lost viability in less than a year.